CD137 in tuberculosis: a scoping review of an emerging immune checkpoint at the crossroads of diagnosis, prognosis, and therapy - Nasir Goronyo, Nuraddin; Chendi, Bih H.; Naidoo, Shalena; Chegou, Novel N. (Frontiers in Immunology, 2025)
IntroductionCD137 (4-1BB), a member of the tumour necrosis factor (TNF) receptor superfamily, plays a key role in T-cell activation, survival, and cytokine production, functions that are central to immune responses against Mycobacterium tuberculosis. This scoping review brings together current evidence on the clinical relevance of CD137 in tuberculosis (TB), including its potential as a diagnostic, prognostic, and therapeutic target.MethodsThis review was conducted in accordance with the PRISMA extension for Scoping Reviews (PRISMA-ScR). Relevant studies on CD137 in TB were identified through database searches and screened using predefined eligibility criteria. Experimental, animal, and human studies reporting on CD137 expression, function, or clinical associations were included. Key information from each study was charted to describe the scope, characteristics, and main findings of the available evidence.ResultsWe identified ten eligible studies involving in vitro experiments, animal models, and human cohorts. CD137-positive T cells and soluble CD137 (sCD137) levels were consistently elevated in active TB, with some evidence suggesting the ability to distinguish disease states and predict severity. Mechanistic studies show that CD137 modulates cytokine responses, including interferon-gamma (IFN-γ) and TNF-α, and interacts with other immune checkpoints such as programmed cell death protein-1 (PD-1) and cytotoxic T-lymphocyte-associated protein-4 (CTLA-4). Preclinical models have demonstrated that CD137-targeted strategies may enhance mycobacterial control. Although current findings are promising, most studies are small, geographically limited, and exploratory.DiscussionCD137 remains an underexplored immune checkpoint with potential to inform host-directed TB diagnostics and therapies, offering a new angle for precision immunology in high-burden settings. Large-scale, longitudinal studies are needed to define its role in host immunity and determine its translational value.